ENDOVASCULAR TREATMENT OF PATIENTS WITH ACUTE THROMBOEMBOLIC OCCLUSION OF THE SUPERIOR MESENTERIC ARTERY - A. I. Khripun; A. B. Mironkov; A. D. Pryamikov; I. N. Tyurin; A. N. Alimov; G. A. Agasyan (Вестник хирургии имени И.И. Грекова, 2020)
THE OBJECTIVE was to report our experience of endovascular treatment in patients with acute thromboembolic occlusion of the superior mesenteric artery (SMA).METHODS AND MATERIALS. 13 patients with acute thromboembolic occlusion of the SMA underwent endovascular intervention. There were 4 (31 %) men and 9 (69 %) women. The average age was 76±9 years. The time from the beginning of the disorder to intervention and mechanical reperfusion of the SMA ranged from 4 to 65 hours, averaging (22±17) hours. Initial leukocytosis was (16.5±5.8)·10/9 l (from 9.2 to 28.8·10/9 l). Various endovascular manipulations were applied to achieve artery reperfusion: mechanical recanalization, balloon angioplasty, aspiration thrombectomy and stenting.RESULTS. Complete recovery of antegrade blood flow through the SMA and its main branches was achieved at all 13 (100 %) patients. Laparotomy was executed at 4 (31 %) patients, thus the intestinal necrosis after endovascular intervention developed in 3 (23 %) cases. The lethal outcome was 46 %. The main reason for a lethal outcome was reperfusion syndrome (4 patients, 31 %).CONCLUSION. Endovascular methods of treatment of patients with acute thromboembolic occlusion of the SMA can be considered as the first step in medical algorithm. They allow to save intestinal viability in most patients. Reperfusion syndrome was the main reason for a lethal outcome. The development of methods for the prevention and treatment of reperfusion syndrome in acute thromboembolic occlusion of the SMA has to become the basis for successful treatment of these patients.